2022
DOI: 10.1177/00914150221143955
|View full text |Cite
|
Sign up to set email alerts
|

Generativity and Engagement in Grandparenting Activities Among Older Adults in Northern Sri Lanka

Abstract: Generativity refers to the desire to pass on one's skills, knowledge, and wisdom to future generations; this may be a clear indicator of the likelihood of older adults investing time and effort in engagement with their grandchildren. This cross-sectional study examines the relationship between generative beliefs and an index of multiple potential grandparenting activities. The data come from a convenience sample of 79 grandparents (aged 55+) living in Sri Lanka, a society experiencing rapid growth in its popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Similarly, Murga and Álvarez (2019) point out that point out that the generative interest manifested in teaching would mobilize teachers towards achieving their goals and general satisfaction with life, promoting self-development and reinforcing their teaching commitment (Quito, 2019). Furthermore, Dohlman et al, (2022) found that some aspects of teaching (e.g., reading stories, helping with homework, being actively involved in caring for future generations, etc. ), operate as a particularly powerful manifestation of the generative beliefs on elderly persons, providing elements of interest for the integration of these behaviors in the teaching culture.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Murga and Álvarez (2019) point out that point out that the generative interest manifested in teaching would mobilize teachers towards achieving their goals and general satisfaction with life, promoting self-development and reinforcing their teaching commitment (Quito, 2019). Furthermore, Dohlman et al, (2022) found that some aspects of teaching (e.g., reading stories, helping with homework, being actively involved in caring for future generations, etc. ), operate as a particularly powerful manifestation of the generative beliefs on elderly persons, providing elements of interest for the integration of these behaviors in the teaching culture.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Western values where preserving individual legacy is paramount, Alaskan Indigenous communities instead prioritize the transfer of spirituality and traditions to younger generations to preserve their community and cultural identity ( Lewis, 2023 ). In Asian cultures where multigenerational households are common, generativity is associated with increased social interaction with children and grandchildren as well as participation in grandparenting activities ( Dohlman et al, 2023 ). Finally, in Ibero-American contexts, family and intergenerational relationships carry significant sociohistorical and cultural importance, marked by frequent intergenerational contact.…”
mentioning
confidence: 99%